Evaluasi Penyesuaian Guru BK dalam Menghadapi Perubahan Layanan Bimbingan dan Konseling pada Era Kurikulum Merdeka di SMA 3 Kerinci - M. Fazli; Yarmis Syukur; Taufik Taufik (Politeknik Kampar, 2025)
The Independent Curriculum brings a paradigm shift in the education process, including in Guidance and Counseling (BK) services. BK teachers are required to adapt to a more humanistic, holistic, and student-needs-based approach. This study aims to evaluate the adjustments made by BK teachers at SMA 3 Kerinci in responding to changes in BK services in the Independent Curriculum. The research method used is descriptive qualitative with interview, observation, and documentation techniques. The results of ithe study indicate that BK teachers have made adjustments through independent training, integration of Pancasila student profiles in BK services, and student-needs-based approaches. However, there are still obstacles in understanding the new paradigm and the limitations of digital media. This study recommends ongoing training and strengthening collaboration between BK teachers and school stakeholders.